The effect of the discovery learning model on fourth-grade students’ understanding of mathematical concepts - Rika Triyuni Duka; C. Asri Budiningsih (Inovasi Kurikulum, 2025)
Elementary school students' low understanding of mathematical concepts is a challenge in the learning process. In the context of the Independent Curriculum, which encourages active and student-centered learning, a learning model that can increase engagement and independence in learning is needed. This study aims to investigate the effect of the Discovery Learning model on the understanding of mathematical concepts of fourth-grade students in Kupang City. Using a quantitative approach with a quasi-experimental method, this study involved two groups: an experimental group that received learning using the Discovery Learning model, and a control group that was taught using the expository method. The research instrument was a conceptual understanding test developed to measure mastery of the material before and after treatment. Data analysis was carried out using the Shapiro-Wilk normality test and the non-parametric Mann-Whitney U test. The test results showed a significance value, indicating a significant difference between student learning outcomes in the two groups. This means that the Discovery Learning model positively contributes to improving students' understanding of mathematical concepts. Further research is recommended to examine the long-term impact of implementing this model and its effectiveness in various mathematical topics and different educational environments.   Absrak Rendahnya pemahaman konsep Matematika peserta didik sekolah dasar menjadi sebuah tantangan dalam proses pembelajaran. Dalam konteks Kurikulum Merdeka yang mendorong pembelajaran aktif dan berpihak pada peserta didik dibutuhkan model pembelajaran yang dapat meningkatkan keterlibatan dan kemandirian belajar. Penelitian ini bertujuan untuk menyelidiki pengaruh model Pembelajaran Penemuan terhadap pemahaman konsep Matematika peserta didik kelas IV di Kota Kupang. Menggunakan pendekatan kuantitatif dengan metode kuasi-eksperimental, penelitian ini melibatkan dua kelompok: kelompok eksperimen yang mendapatkan pembelajaran menggunakan model Pembelajaran Penemuan, dan kelompok kontrol yang diajar dengan metode ekspositori. Instrumen penelitian berupa tes pemahaman konsep yang dikembangkan untuk mengukur penguasaan materi sebelum dan sesudah perlakuan. Analisis data dilakukan melalui uji normalitas Shapiro-Wilk dan uji non-parametrik Mann-Whitney U. Hasil uji menunjukkan nilai signifikansi, yang mengindikasikan adanya perbedaan yang signifikan antara hasil belajar peserta didik di kedua kelompok. Hal ini berarti bahwa model Pembelajaran Penemuan secara positif berkontribusi terhadap peningkatan pemahaman konsep Matematika peserta didik. Penelitian lanjutan disarankan untuk meninjau dampak jangka panjang dari penerapan model ini serta efektivitasnya dalam berbagai topik Matematika dan lingkungan pendidikan yang berbeda. Kata Kunci: model discovery learning; pemahaman konsep Matematika; sekolah dasar